THE EMERGENCE OF NEW MEDIUM - Djaha, Siti Susanti Mallida (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
This study aims at finding the development of new medium of drama in English literary history. From the very first emergence of drama, the plays that have been written were performed in the theater and in many kinds of theater were appears to represent some ideas from the society. As time passing by, these kind of theater had a kind of transformation to be the new medium that we called motion picture. This motion picture began with the silent movie, then it became the talking picture, and it was improved to be the cinema. In its development until today, which we had been known as the movie. This new medium emerged to replace the live theater performance especially in Edwardian era.